2019
DOI: 10.1002/term.2946
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of dermal regeneration using pullulan/gelatin porous skin substitute

Abstract: Tissue-engineered dermal substitutes represent a promising approach to improve wound healing and provide more sufficient regeneration, compared with current clinical standards on care of large wounds, early excision, and grafting of autografts.However, inadequate regenerative capacity, impaired regeneration/degradation profile, and high cost of current commercial tissue-engineered dermal regeneration templates hinder their utilization, and the development of an efficient and costeffective tissue-engineered der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…A previous study by Wong et al showed that pullulan‐collagen hydrogel dressings attenuated macrophage (F4/80 + ) recruitment in hydrogel‐treated wounds compared with Control wounds 12 . Further, Cheng et al observed fewer macrophages in the wound bed of pullulan‐gelatin hydrogel scaffold‐treated wounds compared to controls 33 . Both studies showed improved healing with their respective pullulan hydrogels, indicating that reducing the number of infiltrating macrophages and inflammatory cells within the healing wound bed leads to improved healing outcomes, including mitigation of scar formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Wong et al showed that pullulan‐collagen hydrogel dressings attenuated macrophage (F4/80 + ) recruitment in hydrogel‐treated wounds compared with Control wounds 12 . Further, Cheng et al observed fewer macrophages in the wound bed of pullulan‐gelatin hydrogel scaffold‐treated wounds compared to controls 33 . Both studies showed improved healing with their respective pullulan hydrogels, indicating that reducing the number of infiltrating macrophages and inflammatory cells within the healing wound bed leads to improved healing outcomes, including mitigation of scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Further, Cheng et al observed fewer macrophages in the wound bed of pullulan-gelatin hydrogel scaffold-treated wounds compared to controls. 33 Both studies showed improved healing with their respective pullulan hydrogels, indicating that reducing the number of infiltrating macrophages and inflammatory cells within the healing wound bed leads to improved healing outcomes, including mitigation of scar formation. Although macrophages are essential in wound repair, it has been hypothesized that heavy recruitment of these cell types may delay matrix deposition during the early phases of wound healing due to their phagocytic and enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is regarded as an excellent biomaterial because of its low cost, biodegradability, and biocompatibility. RGD (arginine–glycine–aspartic acid) is the peptide sequence present in gelatin and it helps in cell adherence, growth, and migration of BMSC (bone marrow stromal cells) [ 93 ]. Gel’s properties have enticed several researchers to use it as a bone regeneration material; however, Gel decomposes quickly and has a low mechanical strength.…”
Section: Natural Polymer Nanofibrous Scaffoldmentioning
confidence: 99%
“…Bonding with scaffold materials with certain mechanical strength is required. The artificial dermal scaffold has good biocompatibility [ 28 ], suitable mechanical strength (can resist traction and shear forces) [ 29 ], and has a porous structure conducive to the progress of cell metabolism [ 30 ]. However, the current clinically used artificial dermal materials all have the disadvantage of insufficient vascular regeneration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%